A method for preparing polyimide / silicon dioxide nanocomposite fiber material

Through electrospinning technology, polyamic acid is combined with SiO2 nanospheres to form a continuous fiber structure. Through pre-oxidation treatment, the problem of difficulty in preparing organic/inorganic composite fiber materials with high flexibility and ultra-low thermal conductivity in the prior art is solved, and better thermal insulation and mechanical properties are achieved.

CN116397348BActive Publication Date: 2025-03-14GCL HI TECH NANO MATERIALS (XUZHOU) CO LTD +2
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310515522.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-09
Publication Date
2025-03-14
Estimated Expiration
2043-05-09

AI Technical Summary

Technical Problem

The prior art is difficult to quickly and efficiently prepare organic/inorganic composite fiber materials with high flexibility and ultra-low thermal conductivity, especially when meeting the high requirements of modern industry for thermal insulation and braidability.

Method used

The preparation method of polyimide/silica nanocomposite fiber material is adopted, and the polyamic acid is combined with SiO2 nanospheres through electrospinning technology to form a continuous fiber structure, and the thermal insulation performance of the material is improved by pre-oxidation treatment.

Benefits of technology

The polyimide/silica nanocomposite fiber material with continuous thermal insulation structure, better thermal insulation performance and excellent mechanical properties was achieved, reducing the thermal conductivity of the material and improving flexibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116397348B_ABST
    Figure CN116397348B_ABST
Patent Text Reader

Abstract

A preparation method of a polyimide / silicon dioxide nanocomposite fiber material comprises the following steps: firstly, ammonia water, ethanol and deionized water are uniformly mixed, then tetraethyl orthosilicate is added, and solid SiO2 nanospheres are obtained by centrifugation after stirring; 4,4'-diaminodiphenyl ether is added to N,N-dimethylacetamide, and then pyromellitic anhydride is added after stirring to obtain polyamic acid; polyamic acid and SiO2 nanospheres are added to N,N-dimethylacetamide for mixing, and uniformly stirred to obtain a PAA-SiO2 mixed solution; the PAA-SiO2 mixed solution is centrifuged and then electrostatically spun to obtain a PAA-SiO2 nanofilm material having a continuous fiber structure; and finally, a pre-oxidation treatment is performed in a muffle furnace to obtain a polyimide / silicon dioxide nanocomposite fiber material. The preparation method is simple and low in cost, and the obtained nanocomposite fiber material can have the characteristics of a continuous structure, good flexibility, good thermal insulation, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a method for preparing a polyimide / silicon dioxide nanocomposite fiber material. Background Art

[0002] In recent years, fossil fuel energy consumption and deforestation have been the main causes of global warming. As the global energy crisis continues to worsen, improving energy efficiency and reducing carbon dioxide emissions have become a very important task. Among the many ways to reduce carbon emissions, reducing heat loss during production, transmission and utilization is one of the most important ways and strategies.

[0003] Silica fiber is known for its extremely low thermal conductivity, and it also has the characteristics of high toughness and low density. It can be used as an insulation enhancer to prepare ceramic-based composite materials for thermal insulation, or as a starting material to make fiber aerogels. However, with the increasing requirements of modern industry for the thermal insulation effect and weavability of materials, traditional powdered SiO2 cannot meet the requirements of practical applications. Therefore, further optimizing the microstructure of SiO2 nanomaterials, combining the fiber properties of polymers, and preparing fiber materials with organic / inorganic composites are of great significance to the development of thermal insulation building materials. At present, electrospinning technology is mainly used to prepare organic / inorganic composite fiber materials, such as using PAA as a polymer raw material combined with silica, which effectively improves the flexibility and plasticity of the composite material, but it still cannot achieve the rapid and efficient preparation of composite materials with high flexibility and ultra-low thermal conductivity.

[0004] The existing technology uses carbon vapor deposition to prepare SiO2 nanotube aerogel. Carbon aerogel is used as a sacrificial template and SiO2 nanotube aerogel is prepared by chemical vapor deposition. It is then calcined at high temperature. The high porosity aerogel structure and SiO2 nanotube structure together give it excellent thermal insulation performance, reaching 0.030-0.032W m at room temperature. -1 K -1 However, nano-block SiO2 cannot be quickly woven and planarly composited, and must rely on polymer modeling to prepare highly flexible organic-inorganic composite thermal insulation materials. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a polyimide / silicon dioxide nanocomposite fiber material. The preparation method is simple and low in cost. The obtained polyimide / silicon dioxide nanocomposite fiber material has the characteristics of continuous structure, good flexibility, good thermal insulation and the like.

[0006] To achieve the above object, the present invention provides a method for preparing a polyimide / silicon dioxide nanocomposite fiber material, comprising the following steps:

[0007] S1. Mix ammonia water, ethanol and deionized water in a volume ratio of 1:(7-9):(1-1.2), add a certain amount of tetraethyl orthosilicate, wherein the volume ratio of ammonia water to tetraethyl orthosilicate is 1:(0.4-0.6), stir and react at room temperature for 4-8 hours to obtain a reaction solution, and centrifuge the reaction solution to obtain solid SiO2 nanospheres;

[0008] S2, adding 4,4'-diaminodiphenyl ether to N,N-dimethylacetamide, stirring and then adding pyromellitic acid dianhydride, stirring polymerization for 4-6 hours to obtain polyamic acid; the molar ratio of the 4,4'-diaminodiphenyl ether to pyromellitic acid dianhydride is 1: (0.8-1); the mass volume ratio of the 4,4'-diaminodiphenyl ether to N,N-dimethylacetamide is 1g: (8-10) mL;

[0009] S3, adding the polyamic acid prepared in step S2 and the SiO2 nanospheres prepared in step S1 to N,N-dimethylacetamide, mixing, and stirring to obtain a PAA-SiO2 mixed solution; the mass ratio of the polyamic acid to the SiO2 nanospheres is 1:(0.1-0.2); the mass volume ratio of the polyamic acid to the N,N-dimethylacetamide is 1g:(0.4-0.7)mL;

[0010] S4, centrifuging the PAA-SiO2 mixed solution prepared in step S3 and then performing electrostatic spinning to obtain a PAA-SiO2 nanofilm material having a continuous fiber structure;

[0011] S5. Pre-oxidation treatment of the PAA-SiO2 nano-film material prepared in step S4 in a muffle furnace at 230-280° C. for 3-5 hours to obtain a polyimide / silicon dioxide nano-composite fiber material.

[0012] Preferably, in step S2, the polymerization reaction is carried out in an ice water bath and the temperature is controlled at 0°C.

[0013] Preferably, in step S3, the mass ratio of the polyamic acid to the SiO2 nanospheres is 1:0.15; the mass volume ratio of the polyamic acid to N,N-dimethylacetamide is 1 g:0.5 mL.

[0014] Preferably, in step S3, the stirring speed is 400 r / min and the stirring time is 2 h.

[0015] Preferably, in step S4, the electrospinning positive pressure is 10 kV and the negative pressure is -3 kV; the distance between the spinning needle and the roller receiver is 12 cm; the rotation speed of the roller receiver is 200 r / min; the spinning environment temperature is maintained at 45°C and the humidity is 30%.

[0016] The present invention uses high molecular weight polyamic acid (PAA) as a spinning solution and SiO2 nanospheres as fillers. By adjusting the concentration of PAA and the content of SiO2, the PAA-SiO2 composite fiber film material is prepared by electrostatic spinning technology; and then a polyimide (PI)-SiO2 composite fiber material (P-SiO2) with a continuous structure is prepared after pre-oxidation treatment. Compared with traditional polyamic acid or polyimide polymer matrices, the P-SiO2 composite fiber prepared in the present invention has a continuous insulation structure and better thermal insulation performance.

[0017] In the present invention, SiO2 nanospheres are evenly distributed in the PAA polymer fibers in a relatively dispersed state, which can effectively play a role in heat shielding; SiO2 nanoparticles are well connected by PAA fibers to form a network structure, which significantly improves the flexibility and processability of traditional SiO2 particles. At the same time, compared with the thermal conductivity of PAA polymer of 0.034W m -1 K -1 The composite nanofiber membrane (P-SiO2) obtained by this method exhibits ultra-low thermal conductivity (0.023 W m -1 K -1 ) and excellent mechanical properties, bringing great prospects for the development of thermal insulation materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 is a SEM image of SiO2 nanospheres prepared by a solution method in Example 1 of the present invention;

[0019] Figure 2 These are optical images of the P-SiO2 nanocomposite fiber material prepared in Example 1 of the present invention, (a) a large sheet of P-SiO2 film; (b) a display of the flexibility of the P-SiO2 film;

[0020] Figure 3 This is a SEM image of the P-SiO2 nanocomposite fiber material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0021] The present invention is further described in detail below in conjunction with specific embodiments.

[0022] Example 1

[0023] A method for preparing a polyimide / silicon dioxide nanocomposite fiber material comprises the following steps:

[0024] S1. 9.8 mL of ammonia water, 73.8 mL of ethanol and 10.8 mL of deionized water were mixed evenly, and then 5.4 mL of tetraethyl orthosilicate (TEOS) was added, and the mixture was stirred at room temperature for 6 h to obtain a reaction solution, and the reaction solution was centrifuged to obtain solid SiO2 nanospheres, whose SEM image is shown in FIG. Figure 1 As shown in the figure, it can be seen that the average diameter of the prepared SiO2 template is about 270nm, which is monodisperse and has obvious boundaries;

[0025] S2, adding 5.52 g of 4,4'-diaminodiphenyl ether (ODA) to 50 mL of N,N-dimethylacetamide (DMAC), mechanically stirring, then adding 4.41 g of pyromellitic dianhydride (PMDA), and polymerizing in an ice-water bath for 5 h, the temperature was controlled at 0°C, the reaction solution gradually turned slightly yellow, and the viscosity increased, to obtain polyamic acid (PAA);

[0026] S3, add 2g PAA into a single-necked flask containing 1.0mL DMAC, stir mechanically to make it uniformly dispersed, then add 0.3g SiO2 nanospheres, stir further to make it uniformly dispersed, the stirring speed is 400r / min, the stirring time is 2h, and a PAA-SiO2 mixed solution is obtained;

[0027] S4, the PAA-SiO2 mixed solution prepared in step S3 is placed in a 5 mL centrifuge tube, and electrospinning is performed after centrifugation to obtain a PAA-SiO2 nanofilm material with a continuous fiber structure; the electrospinning parameters are as follows: the electrospinning positive pressure is 10 kV, the negative pressure is -3 kV; the distance between the spinning needle and the roller receiver is 12 cm; the rotation speed of the roller receiver is 200 r / min; the spinning environment temperature is maintained at 45°C and the humidity is 30%;

[0028] S5. The fiber film PAA-SiO2 nanocomposite material prepared in step S4 was heated from room temperature to 250°C in a muffle furnace, and the temperature was maintained for pre-oxidation treatment for 3 hours. The sample was naturally cooled and taken out. The sample turned yellow to obtain a polyimide (PI)-SiO2 nanocomposite fiber material. The optical image and SEM image are shown as follows: Figure 2 and Figure 3 As shown, from Figure 2 It can be seen that the material has good flexibility and processability. Figure 3 It can be seen that the material has a continuous fiber structure.

[0029] The polyamic acid PAA polymer prepared in step S2 of this embodiment showed the highest thermal conductivity of 0.034 Wm -1 K -1 The thermal conductivity of P-SiO2 prepared in this example is 0.023 W m -1 K -1 , indicating that the addition of SiO2 nanospheres played a key role in reducing the thermal conductivity.

[0030] Example 2

[0031] A method for preparing a polyimide / silicon dioxide nanocomposite fiber material comprises the following steps:

[0032] S1. 9.8 mL of aqueous ammonia, 68.6 mL of ethanol and 9.8 mL of deionized water were mixed evenly, and then 3.92 mL of tetraethyl orthosilicate (TEOS) was added, and the mixture was stirred at room temperature for 8 h to obtain a reaction solution, and the reaction solution was centrifuged to obtain solid SiO2 nanospheres;

[0033] S2, adding 5.52 g of 4,4'-diaminodiphenyl ether (ODA) to 44 mL of N,N-dimethylacetamide (DMAC), mechanically stirring, then adding 4.41 g of pyromellitic dianhydride (PMDA), and polymerizing in an ice-water bath for 4 h, the temperature was controlled at 0°C, the reaction solution gradually turned slightly yellow, and the viscosity increased, to obtain polyamic acid (PAA);

[0034] S3, add 2g PAA into a single-necked flask containing 0.8mL DMAC, stir mechanically to make it uniformly dispersed, then add 0.2g SiO2 nanospheres, stir further to make it uniformly dispersed, the stirring speed is 400r / min, the stirring time is 2h, and a PAA-SiO2 mixed solution is obtained;

[0035] S4, the PAA-SiO2 mixed solution prepared in step S3 is placed in a 5 mL centrifuge tube, and electrospinning is performed after centrifugation to obtain a PAA-SiO2 nanofilm material with a continuous fiber structure; the electrospinning parameters are as follows: the electrospinning positive pressure is 10 kV, the negative pressure is -3 kV; the distance between the spinning needle and the receiver is 12 cm; the rotation speed of the drum receiver is 200 r / min; the spinning environment temperature is maintained at 45°C and the humidity is 30%;

[0036] S5. Heat the fiber film PAA-SiO2 nanocomposite material prepared in step S4 from room temperature to 250°C in a muffle furnace, maintain this temperature for pre-oxidation treatment for 3 hours, cool naturally, take out the sample, the sample becomes yellowish, and obtain a polyimide (PI)-SiO2 nanocomposite fiber material having a continuous fiber structure and good flexibility.

[0037] Example 3

[0038] A method for preparing a polyimide / silicon dioxide nanocomposite fiber material comprises the following steps:

[0039] S1. 9.8 mL of aqueous ammonia, 88.2 mL of ethanol and 11.8 mL of deionized water were mixed evenly, 5.9 mL of tetraethyl orthosilicate (TEOS) was added thereto, and the mixture was stirred and reacted at room temperature for 6 h to obtain a reaction solution, and the reaction solution was centrifuged to obtain solid SiO2 nanospheres;

[0040] S2, adding 5.52 g of 4,4'-diaminodiphenyl ether (ODA) to 55 mL of N,N-dimethylacetamide (DMAC), stirring mechanically, then adding 5.52 g of pyromellitic dianhydride (PMDA), and polymerizing in an ice-water bath for 6 h, the temperature was controlled at 0°C, the reaction solution gradually turned yellow, and the viscosity increased, to obtain polyamic acid (PAA);

[0041] S3, add 2g PAA into a single-necked flask containing 1.4mL DMAC, stir mechanically to make it uniformly dispersed, then add 0.4g SiO2 nanospheres, stir further to make it uniformly dispersed, the stirring speed is 400r / min, the stirring time is 2h, and a PAA-SiO2 mixed solution is obtained;

[0042] S4, the PAA-SiO2 mixed solution prepared in step S3 is placed in a 5 mL centrifuge tube, and electrospinning is performed after centrifugation to obtain a PAA-SiO2 nanofilm material with a continuous fiber structure; the electrospinning parameters are as follows: the electrospinning positive pressure is 10 kV, the negative pressure is -3 kV; the distance between the spinning needle and the receiver is 12 cm; the rotation speed of the drum receiver is 200 r / min; the spinning environment temperature is maintained at 45°C and the humidity is 30%;

[0043] S5. Heat the fiber film PAA-SiO2 nanocomposite material prepared in step S4 from room temperature to 250°C in a muffle furnace, maintain this temperature for pre-oxidation treatment for 3 hours, cool naturally, take out the sample, the sample becomes yellowish, and obtain a polyimide (PI)-SiO2 nanocomposite fiber material having a continuous fiber structure and good flexibility and processability.

Claims

1. A method for preparing a polyimide / silicon dioxide nanocomposite fiber material, characterized in that: The following steps are involved: S1. Mix ammonia water, ethanol and deionized water in a volume ratio of 1: (7-9): (1-1.2), add a certain amount of tetraethyl orthosilicate, wherein the volume ratio of ammonia water to tetraethyl orthosilicate is 1: (0.4-0.6), stir and react at room temperature for 4-8 h to obtain a reaction solution, and centrifuge the reaction solution to obtain solid SiO2 nanospheres; S2, adding 4,4'-diaminodiphenyl ether to N,N-dimethylacetamide, stirring and then adding pyromellitic acid dianhydride, stirring polymerization for 4-6 h to obtain polyamic acid; the molar ratio of the 4,4'-diaminodiphenyl ether to pyromellitic acid dianhydride is 1: (0.8-1); the mass volume ratio of the 4,4'-diaminodiphenyl ether to N,N-dimethylacetamide is 1 g: (8-10) mL; S3, adding the polyamic acid prepared in step S2 and the SiO2 nanospheres prepared in step S1 into N,N-dimethylacetamide, mixing, and stirring to obtain a PAA-SiO2 mixed solution; the mass ratio of the polyamic acid to the SiO2 nanospheres is 1:0.15; the mass volume ratio of the polyamic acid to the N,N-dimethylacetamide is 1 g: (0.4-0.7) mL; S4, centrifuging the PAA-SiO2 mixed solution prepared in step S3 and then performing electrostatic spinning to obtain a PAA-SiO2 nanofilm material having a continuous fiber structure; S5. Pre-oxidation treatment of the PAA-SiO2 nano-film material prepared in step S4 is performed in a muffle furnace at 230-280° C. for 3-5 h to obtain a polyimide / silicon dioxide nano-composite fiber material.

2. The method for preparing a polyimide / silicon dioxide nanocomposite fiber material according to claim 1, characterized in that: In step S2, the polymerization reaction is carried out in an ice water bath, and the temperature is controlled at 0°C.

3. The method for preparing a polyimide / silicon dioxide nanocomposite fiber material according to claim 1, characterized in that: In step S3, the mass volume ratio between the polyamic acid and N,N-dimethylacetamide is 1 g:0.5 mL.

4. The method for preparing a polyimide / silicon dioxide nanocomposite fiber material according to claim 1, characterized in that: In step S3, the stirring speed is 400 r / min and the stirring time is 2 h.

5. The method for preparing a polyimide / silicon dioxide nanocomposite fiber material according to claim 1, characterized in that: In step S4, the electrospinning positive pressure used was 10 kV and the negative pressure was -3 kV; the distance between the spinning needle and the roller receiver was 12 cm; the rotation speed of the roller receiver was 200 r / min; the spinning environment temperature was maintained at 45°C and the humidity was 30%.

Citation Information

Cited By

  • Butyl acrylate-based polymeric dispersant for polyimide foam as well as preparation method and application of butyl acrylate-based polymeric dispersant

    CN121949672A